GENERAL CONCEPTS OF PHRASEOLOGICAL UNITS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Phraseology is being studied as one of the subjects of linguistics. Phraseology discusses phraseologies that are stable word connections in a particular language. Phraseologisms, words and phrases before thinking about its properties need to know the connection. This thesis discusses the General concept of phraseological units.